2010
DOI: 10.1097/bsd.0b013e3181cf07ee
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Perioperative Oral Multimodal Analgesia Versus IV PCA for Spine Surgery

Abstract: This quality improvement study shows some safety and significant advantages of a multimodal perioperative oral analgesic regimen compared with standard IV PCA after spine surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
56
0
4

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(63 citation statements)
references
References 22 publications
3
56
0
4
Order By: Relevance
“…14,15 Multimodal pain control strategies for certain procedures could become an integral part of clinical pathways to provide effective postoperative analgesia and rehabilitation. 16,17 …”
Section: Multimodal Analgesiamentioning
confidence: 98%
“…14,15 Multimodal pain control strategies for certain procedures could become an integral part of clinical pathways to provide effective postoperative analgesia and rehabilitation. 16,17 …”
Section: Multimodal Analgesiamentioning
confidence: 98%
“…Most of the clinical trials have used oral 600 mg of gabapentin before surgery (1 hour before surgery) and continued (gabapentin at 600 mg 2 or 3 times a day) for the next 5 to 14 days depending on the extent of surgical trauma. 30 Pregabalin at a dose of 100 to 150 mg before surgery and continued in the postoperative period at a dose of 75 mg twice a day has been used in multiple joint replacement surgical patients and resulted in decreased acute and chronic pain in randomized controlled designs. 31 However, at this point, the exact dosing and duration need to be properly established to avoid the sedative side effects of gabapentinoids.…”
Section: Preoperative Periodmentioning
confidence: 99%
“…Similarly, retrospective studies by Mathiesen, et al [6] and Rajpal, et al [39] demonstrated decreased total narcotic consumption and lower pain scores, as well as fewer adverse side effects such as nausea, vomiting, constipation, drowsiness, coughing and difficulty with deep breathing. An added benefit that has been demonstrated with MMA is shorter time to mobilization and reduced length of hospital stays [6,40] Despite decreased narcotic utilization with MMA protocols, total cost of medication has been reported to be similar between MMA and PCA groups [39]. However, this analysis did not take in to account the up front cost of equipment needed with PCA.…”
Section: Introductionmentioning
confidence: 99%